NELL1 membranous nephropathy: clinical associations provide mechanistic clues - Andeen, Nicole K.; Kung, Vanderlene L.; Avasare, Rupali S. (Frontiers in Nephrology, 2024)
Neural epidermal growth factor-like 1 (NELL1) membranous nephropathy (MN) is notable for its segmental deposit distribution, IgG1 dominant deposits, and comparatively high rate of spontaneous remission. It has been associated with a variety of exposures and secondary conditions, specifically use of thiol-containing medications – including lipoic acid, bucillamine, and tiopronin – as well as traditional indigenous medications (TIM) particularly those with high mercury content, and non-steroid anti-inflammatory drugs (NSAIDs). Malignancies, graft vs. host disease (GVHD), infection, and autoimmune conditions have also been associated with NELL1 MN. Herein, we provide a detailed summary of the clinicopathologic features of NELL1 and associations with underlying conditions, with a focus on treatment and outcomes. Rare cases of dual NELL1 and phospholipase A2 receptor (PLA2R) positive MN are reviewed. Genome-wide association study of NELL1, role of NELL1 in other physiologic and pathologic processes, and connection between NELL1 MN and malignancy with relevance of NELL1 tumor staining are examined. Finally, relationships and potential disease mechanisms of thiol- and mercury- associated NELL1 MN are discussed.